Review: The multiple roles of plant lectins - De Coninck, Tibo; Van Damme, Els J.M. (Plant science (Limerick), 2021)
•Plant lectins are a diverse group, present in multiple cell compartments.•Lectin domains can be linked to other protein domains.•Lectins are versatile, more than carbohydrate-binding proteins.•Lectins play roles in plant immunity, stress signaling, gene regulation, defense. For decades, the biological roles of plant lectins remained obscure and subject to speculation. With the advent of technological and scientific progress, researchers have compiled a vast amount of information regarding the structure, biological activities and functionality of hundreds of plant lectins. Data mining of genomes and transcriptome sequencing and high-throughput analyses have resulted in new insights. This review aims to provide an overview of what is presently known about plant lectins, highlighting their versatility and the importance of plant lectins for a multitude of biological processes, such as plant development, immunity, stress signaling and regulation of gene expression. Though lectins primarily act as readers of the glycocode, the multiple roles of plant lectins suggest that their functionality goes beyond carbohydrate-recognition.